A redox-active fluorescent ph indicator for detecting plasmodium falciparum strains with reduced responsiveness to quinoline antimalarial drugs - Jida, Mouhamad; Sanchez, Cecilia P.; Ehrhardt, Katharina; Lanzer, Michael (ACS infectious diseases, 2017)
Mutational changes in the Plasmodium falciparum chloroquine resistance transporter (PfCRT) have been associated with differential responses to a wide spectrum of biologically active compounds including current and former quinoline and quinoline-like antimalarial drugs. PfCRT confers altered drug responsiveness by acting as a transport system, expelling drugs from the parasite’s digestive vacuole where these drugs exert, at least part of, their antiplasmodial activity. To preserve the efficacy of these invaluable drugs, novel functional tools are required for epidemiological surveys of parasite strains carrying mutant PfCRT variants and for drug development programs aimed at inhibiting or circumventing the action of PfCRT. Here we report the synthesis and characterization of a pH-sensitive fluorescent chloroquine analogue consisting of 7-chloro-N-{2-[(propan-2-yl)amino]ethyl}quinolin-4-amine functionalized with the fluorochrome 7-nitrobenzofurazan (NBD) (henceforth termed Fluo-CQ). In the parasite, Fluo-CQ accumulates in the digestive vacuole, giving rise to a strong fluorescence signal but only in parasites carrying the wild type PfCRT. In parasites carrying the mutant PfCRT, Fluo-CQ does not accumulate. The differential handling of the fluorescent probe, combined with live cell imaging, provides a diagnostic tool for quick detection of those P. falciparum strains that carry a PfCRT variant associated with altered responsiveness to quinoline and quinoline-like antimalarial drugs. In contrast to the accumulation studies, chloroquine (CQ)-resistant parasites were observed cross-resistant to Fluo-CQ when the chemical probe was tested in various CQ-sensitive and -resistant parasite strains. NBD derivatives were found to act as redox cyclers of two essential targets, using a coupled assay based on methemoglobin and the NADPH-dependent glutathione reductase (GRs) from P. falciparum. This redox activity is proposed to contribute to the dual action of Fluo-CQ on redox equilibrium and methemoglobin reduction via PfCRT-mediated drug efflux in the cytosol and then continuous redox-dependent shuttling between food vacuole and cytosol. Taking into account these physicochemical characteristics, a model was proposed to explain Fluo-CQ antimalarial effects involving the contribution of PfCRT-mediated transport, methemoglobin reduction, hematin binding, and NBD reduction activity catalyzed by PfGR in CQ-resistant versus CQ-sensitive parasites. Therefore, introduction of NBD fluorophore in drugs is not inert and should be taken into account in drug transport and imaging studies.